(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
We here propose a revision of the stratigraphic interval comprised between the top of platform carbonates, mainly of Early Jurassic age, and the base of the Maiolica, in the Trento Plateau. Most of this interval (upper Bajocian - upper Tithonian) is represented by ammonite-bearing, red nodular limestones known with the historical name of Rosso Ammonitico Veronese (RAV). It has been subdivided in three units: a lower unit, calcareous and massively bedded; a middle unit, thinly bedded and cherty; and an upper unit, calcareous and nodular. In addition to these units, other sedimentary bodies are known below the base of the RAV. These are thin and discontinuous, such as the Lumachella a Posidonia alpina (LPa) and the Calcari a Skirroceras (CSk), both spanning the upper Aalenian - upper Bajocian. A lithostratigraphic redefinition of the RAV is proposed by addition of two members (LPa e CSk) to the three classical members. The new members are easily distinguished by their lithofacies and are always separated from the lower unit by discontinuities. Two sections located on the Altopiano di Asiago are described: Kaberlaba shows all the three members (lower, middle and upper) and is proposed as the reference section for a formalization of the RAV; Rabeschini is characterized by the absence of the middle member and may be held as a complementary section. The RAV lower boundary is everywhere very sharp and marked by a facies contrast; the upper boundary, instead, is transitional and is defined by a progressive change from red, nodular, Saccocoma packstones to white, non-nodular calpionellid wackestones. Calpionellid associations indicate that the upper boundary falls within the upper Tithonian.